Antimicrobial Catanionic Vesicular Self‐Assembly with Improved Spectrum of Action. Issue 5 (7th February 2013) - Chaouat, Clara; Balor, Stéphanie; Roques, Christine; Franceschi‐Messant, Sophie; Perez, Emile; Rico‐Lattes, Isabelle
Abstract: A catanionic mixture based on three components, N ‐dodecyldiethanolamine, decanoic acid and azelaic acid, was prepared and investigated from a physico‐chemical point of view and for its antimicrobial activity. The spontaneously formed vesicles were characterized by dynamic light scattering, zeta potential and electron microscopy. These experiments showed spherical vesicles with an average diameter of 200 nm and a zeta potential of +22 mV. The antimicrobial activity of the vesicle dispersion against different strains ( Staphylococcus aureus, Escherichia coli, Staphylococcus epidermidis, Propionibacterium acnes and Candida albicans ), was evaluated and compared with the activity of the components separately. The synergistic effect of these bioactive self‐assembled catanionic vesicles on the spectrum of activity and on the cytoplasmic membrane is discussed.